REGIONAL MARKETING MANAGEMENT STRATEGY IN ENHANCING TOURISM COMPETITIVENESS IN RIAU PROVINCE - Ul-Fa Niah; Siti Rofidah; Rizqi Fakhri; Teuku Reza Kurniawan; Iskandar (CV. Radja Publika, 2026)
This study aims to formulate an effective regional marketing management strategy to enhance the tourism competitiveness of Riau Province, Indonesia. Despite its rich natural and cultural tourism potential, Riau has not yet achieved optimal competitiveness compared to other leading destinations. This study employs a qualitative descriptive approach using purposive sampling, involving 12 informants consisting of government officials, tourism business actors, and local community representatives. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using thematic analysis based on the Miles and Huberman framework. The findings reveal four major issues: (1) tourism marketing strategies remain conventional and lack market orientation, particularly in segmentation, targeting, and positioning; (2) destination branding is weak and inconsistent, resulting in a fragmented tourism image; (3) stakeholder collaboration is limited and characterized by poor coordination and low community involvement; and (4) digital marketing utilization is suboptimal due to limited technological capacity and lack of integrated platforms. These findings indicate a structural gap between tourism potential and marketing management effectiveness. The study concludes that improving tourism competitiveness in Riau requires a comprehensive and integrated approach, including strengthening destination branding, enhancing stakeholder collaboration, and accelerating digital transformation. The research contributes to the literature by emphasizing the importance of marketing system maturity, institutional coordination, and digital readiness in regional tourism development. Practically, the study provides strategic recommendations for policymakers and tourism stakeholders to develop a more competitive and sustainable tourism sector.